Comparative analysis of woody species diversity in church, community, and national park forests in Ethiopia: Review - Sewagegn, Geremew (Center for Science and Technology, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Forest resources in Ethiopia are facing intensive degradation and deforestation due to agricultural land expansion, overgrazing, urbanization, invasive species, and climate change. Due to this, small isolated forest patches are left in different parts of the country through legal protections and religious sanctions. The study aimed to examine the country's highest woody species diversity among church, community, and national park forests. The remnant forest patches in Ethiopia were categorized into church, community, and national park forests based on ownership and management objectives of the forest. The diversity data were collected from a detailed review of published and unpublished scientific reports. The variation in species richness, evenness, and Shannon diversity among forest categories were analyzed and tested using ANOVA. The mean Shannon diversity of church, community, and national park forests were 2.95, 2.88, and 3.13, respectively. These forest categories have a considerable role in species diversity in the country. However, the variation was statistically insignificant at a 95% confidence interval. Hence, each forest category plays a comparable role in woody species diversity in the country.